'A Few Human Hearts in Catholic Breasts': Angina Pectoris, Emotions, and Kate O'Brien's Mary Lavelle. Issue 1 (May 2018) - O'Neill, Margaret
Abstract : This article reads Kate O'Brien's Mary Lavelle in a cultural historical framework of medicine and psychoanalysis to explore the significance of the heart condition angina pectoris in the text. The novel illuminates the complexities of the mind-body relationship, the connections between emotional trauma and bodily symptoms, and cultural constructions of masculinity and femininity within the historical conditions and medical models that have shaped them. Ultimately, Mary Lavelle undermines the primacy of objectivity and rationality encoded in ideals of masculinity that guide cultural and medical discourses. The novel furthermore speaks to the imperative to listen to the narratives spoken through patient's bodies.